Perancangan Model Bisnis Perusahaan Training dan Consulting PT.XYZ dengan Menggunakan Business Model Canvas - Laila Putri Faradilah; Endang Chumaidiyah; Farda Hasun (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
PT. XYZ is a company engaged in Business Training & Consulting located in the city of Bandung. PT. XYZ was established in 2012. Currently, the company cannot achieve its annual revenue target. This is due to problems in terms of marketing such as the absence of employer partners and limited marketing activities, limited employees, to increasingly fierce business competition in similar fields. Solutions to the problems experienced by PT. XYZ can be overcome through evaluation of the current business model so that the best solution can be found from the existing problems with the role of the proposed business model. Business model design is carried out using the Business Model Canvas (BMC) method. Currently there is one customer segment served by PT. XYZ is a company located in the West Java area with revenues of more than Rp 4,000,000.00 per month and has Islamic value. Data collection was obtained from interviews with customers to find out customer profile and business model environment and questionnaires were distributed to determine SWOT by utilizing internal company resources. From the results of the data analysis obtained, a business model canvas was then designed and verification and validation were carried out. Verification is carried out with research supervisors and owners of PT. XYZ. Furthermore, the proposed business model will be designed a mockup that will be used for the validation process to the owner of PT. XYZ. The design results obtained in this study are making improvements to the customer segment block by expanding the customer segment in Indonesia, the customer relationship block by providing service guarantees, feedback facilities and service incentives, channel blocks by participating in MSME events, value proposition blocks by adding service bundling packages, service variations, services through the website so that they are easily accessible and create product substitutions, and in the key partner block of PT. XYZ can collaborate with INKINDO, the organizer of MSME events to develop their business. By implementing this proposed business model, PT. XYZ hopes to increase annual revenue targets and improve business performance to reach potential markets.PT. XYZ is a company engaged in Business Training & Consulting located in the city of Bandung. PT. XYZ was established in 2012. Currently, the company cannot achieve its annual revenue target. This is due to problems in terms of marketing such as the absence of employer partners and limited marketing activities, limited employees, to increasingly fierce business competition in similar fields. Solutions to the problems experienced by PT. XYZ can be overcome through evaluation of the current business model so that the best solution can be found from the existing problems with the role of the proposed business model. Business model design is carried out using the Business Model Canvas (BMC) method. Currently there is one customer segment served by PT. XYZ is a company located in the West Java area with revenues of more than Rp 4,000,000.00 per month and has Islamic value. Data collection was obtained from interviews with customers to find out customer profile and business model environment and questionnaires were distributed to determine SWOT by utilizing internal company resources. From the results of the data analysis obtained, a business model canvas was then designed and verification and validation were carried out. Verification is carried out with research supervisors and owners of PT. XYZ. Furthermore, the proposed business model will be designed a mockup that will be used for the validation process to the owner of PT. XYZ. The design results obtained in this study are making improvements to the customer segment block by expanding the customer segment in Indonesia, the customer relationship block by providing service guarantees, feedback facilities and service incentives, channel blocks by participating in MSME events, value proposition blocks by adding service bundling packages, service variations, services through the website so that they are easily accessible and create product substitutions, and in the key partner block of PT. XYZ can collaborate with INKINDO, the organizer of MSME events to develop their business. By implementing this proposed business model, PT. XYZ hopes to increase annual revenue targets and improve business performance to reach potential markets.